Effect of Chemically Altered Litter on Welfare Parameters of Commercial Broiler Chicken - Patel, Jigar V.; Trivedi, Manoj M.; Rajpura, Rais M.; Modi, Rakesh J. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The experiment was conducted to study the effect of chemically treated litter on the welfare parameters of commercial broiler chicken. A total of 144 straight-run day-old commercial broiler chicks were distributed randomly into six treatment groups, each group consisted of four replications, each of 6 chicks. The experiment was conducted in two different seasons, winter and monsoon, each of 6 weeks duration. The treatments included: T1 (control, rice husk as litter material); T2 (rice husk litter treated with alum @ 90 g/sq.ft.), T3 (litter treated with boric acid, H3BO3, @ 24 g/sq.ft.; T4 (litter altered with sodium bisulphate (NaHSO4) @ 25 g/sq.ft.); T5 (litter treated with commercially available probiotic product @ 1 g/ sq.ft); and T6 (litter treated with commercially available Yucca schidigera liquid solution @ 1.0 mL/ sq.ft). The chemical alteration of litter (T2 to T6) was done on the 1st, 15th and 29th days of the experiment period. The footpad percentage was found higher in T2 followed by T6, T3, T4, T5, and T1 in both the seasons. You are advised to check again carefully this statement is not correct , you should be sincere , if you are unable to do yourself , take help from some one it is very tedious for us to cross check every time ) The hock burn percentage was found higher in T2 in both seasons followed by T3, T6, T4, T5, and T1 in winter and by T3, T4, T6, T5, and T1 in monsoon. A higher 0 score percentage indicated improved welfare parameters. In both seasons, there were no blister sores on the breast. Based on the overall result of the present experiment, it can be concluded that the broiler birds reared on rice husk litter material treated or amended with alum @ 90 g/sq.ft had decreased the footpad and hock burn lesions than the control and other treatment groups.
Keywords: Broiler chicken; Commercial; Litter amendment; Welfare parameter